Peningkatan Kemampuan Menjumlahkan dan Mengurangkan Bilangan Bulat Melalui Permainan Engklek Siswa Kelas IV SD Negeri Geneng 1 Semester 1 Kabupaten Sragen Tahun 2015/2016 - Fajarwati, Ariskha Lianasari (2016)
The analysis of daily tests for the subject matter in the summing and subtracting integers only 20 % or 4 out of 20 students who achieve a minimum completeness criteria ( KKM ) of 65 on the charge of Mathematics . Things that cause low ability of teaching and learning mathematics is boring . This research aims to improve learning outcomes addition and subtraction of integers in Mathematics Elementary School fourth grade students Geneng 1 semester 1 2015/2016. This research is a form of action research consists of two cycles , each cycle consisting of four phases : planning , implementation , observation , and reflection . As a research subject is the 4^th grade students of SD Negeri Geneng 1. Data collection technique used observation , interview , documentation and testing . Data were analyzed using an interactive model analysis technique that consists of data reduction , display or presentation of data , and make decisions and then verified. The results showed an increase in ability to add and subtract of integers. It can be seen from the acquisition of indicators of achievement. Percentage of completeness in the first cycle at 65% or 13 students while yet achieve mastery of 35% or 7 students, with an average grade of 66.9. Percentage of completeness in the second cycle of 90% or 18 students who do not achieve mastery while only 10% or 2 students., With an average grade of 78.3. The study concluded that the application of the engklek game can increase in ability to add and subtract of integers. Keywords: ability, engklek game, to add and subtract of integers.